NUMERICAL APPROACHES TO SOCIAL MOBILITY: MODELLING THE IMPACT OF EDUCATION AND ECONOMIC FACTORS - B.A, Ashwakh Ahamed (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research employs a numerical approach, specifically Agent-Based Modeling (ABM), to investigate the dynamics of social mobility within a hypothetical society. Utilizing simulated scenarios, the study explores the influence of education and economic factors on individual trajectories and societal outcomes. The findings reveal a positive correlation between education levels and social mobility, emphasizing the crucial role of educational opportunities. Additionally, economic indicators exhibit a significant impact on upward mobility. The study contributes to sociological understanding by bridging theoretical frameworks with empirical observations through numerical simulations, providing insights for evidence-based social policies.